2019
DOI: 10.2174/1570159x16666180702144644
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Cannabinoid System: A New Perspective for the Treatment of the Alzheimer’s Disease

Abstract: The pathogenesis of Alzheimer's disease (AD) is somewhat complex and has yet to be fully understood. As the effectiveness of the therapy currently available for AD has proved to be limited, the need for new drugs has become increasingly urgent. The modulation of the endogenous cannabinoid system (ECBS) is one of the potential therapeutic approaches that is attracting a growing amount of interest. The ECBS consists of endogenous compounds and receptors. The receptors CB1 and CB2 have already been well character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 78 publications
2
45
0
1
Order By: Relevance
“…Several studies demonstrated that eCBs act as immunomodulators by inhibiting cytokine and chemokine production and microglial cell activation [ 42 , 43 ]. To validate our experimental settings, we assessed Aβ 25–35 induced microglia activation, which was partially counteracted by URB597, evaluating both the immunofluorescence signal of Iba1-positive cells and the Iba1 protein level, supporting the efficacy of URB597 on FAAH activity in BV-2 cells [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated that eCBs act as immunomodulators by inhibiting cytokine and chemokine production and microglial cell activation [ 42 , 43 ]. To validate our experimental settings, we assessed Aβ 25–35 induced microglia activation, which was partially counteracted by URB597, evaluating both the immunofluorescence signal of Iba1-positive cells and the Iba1 protein level, supporting the efficacy of URB597 on FAAH activity in BV-2 cells [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The retrograde endocannabinoid signalling system is a lipid-based neuromodulatory system with important roles in the CNS including in physiological and neurodegenerative processes [94,95]. It has been associated to pathogenesis of PD as well as AD and ischemia [95][96][97] and suggested as a therapeutic target for treatment of a range of neurodegenerative disorders including AD, PD, HD, multiple sclerosis (MS), and ALS [98][99][100]. Putative roles for its regulation via post-translational deimination have not been previously identified and therefore bring a novel angle of modulation of endocannabinoid signalling pathways in neurodegeneration, including in early disease stages.…”
Section: Discussionmentioning
confidence: 99%
“…The ECS and its components have been widely studied in search for therapeutics for PD and AD [62,63]. The coexpression of CB1R and GPR55 has shown a significant neuroprotection against parkinsonism-inducing MPP + toxin [64].…”
Section: The Endocannabinoid Systemmentioning
confidence: 99%